Psychometric Properties of the Korean Version of the Mental Health Professionals Stress Scale - Lee, Eun Sol; Ryu, Vin; Lee, Ji Hyun; Hong, Hyeon; Han, Hyeree; Park, Subin (Frontiers in Psychiatry, 2021)
Background: Job stress of mental health professionals can have a negative impact on them, particularly their psychological health and mortality, and may also affect organizations’ and institutions’ ability to provide quality mental health services to patients. Aim: This study aimed to: (1) investigate the validity and reliability of the Korean Mental Health Professionals Stress Scale (K-MHPSS), (2) develop K-MHPSS cut-off points to measure clinical depression and anxiety, and (3) examine whether specific stressors vary by area of expertise. Methodology: Data were collected via an online survey over three months, from August to October 2020. An online survey using a survey website was administered to volunteers who accessed the link and consented to participate. Data from 558 participants (200 clinical psychologists, 157 nurses, and 201 social workers) were included in the final analysis. Confirmatory and exploratory factor analyses were conducted to examine the factor structure of the K-MHPSS; concurrent validity of the scale was determined by analyzing correlation; internal consistency was determined by Cronbach’s alpha coefficient. In addition, ROC curve analysis and Youden’s index were used to estimate optimal cut-off points for K-MHPSS; one-way ANOVA was performed to investigate the difference among the three groups. Results: The seven-factor model of the original scale did not be replicated by Korean mental health professionals. The K-MHPSS had the best fit with the six-factor model, which consists of 34 items. Concurrent validity was confirmed, and overall reliability was found to be good. The K-MHPSS cut-off points for depression and anxiety appeared to slightly different by professional groups. Furthermore, nurses and social workers showed significantly higher total scores compared to clinical psychologists, and there are significant differences in subscale scores among professionals. Conclusion: The Korean version of the MHPSS has appropriate psychometric properties and can be used to assess the occupational stress of mental health professionals. It can also serve as a reference point for screening clinical level of depression and anxiety in mental health professionals